HOAX AND LAW ENFORCEMENT IN THE POST-TRUTH ERA IN A PRORESSIVE LEGAL PERSPECTIVE - Ari Nurhaqi (International Peneliti Ekonomi, Sosial dan Teknologi, 2023)
The phenomenon of reporting and spreading hoaxes on social media to drive public opinion is packaged in the concept of post-truth, where a pattern of a lie that is told repeatedly will disguise itself as the truth. Ignoring this will have an impact on the emergence of panic, hatred, anxiety, commotion, insecurity, fear, damage to reputation and can even lead to social movements and divisions in society. Law enforcement efforts with a responsive legal approach offer liberation from types, ways of thinking, not only texts, but also contexts, so as to place certainty, justice and benefit in one breath. The application of all of the above dimensions does not only affect the law from the process of its occurrence to its enforcement, but in particular will result in consistency in law enforcement without being selective (discriminatory) in accordance with the legal principle that all people are equal before the law (equality before the law).